2005
DOI: 10.1007/bf03030524
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of ambient solar uv (280-400 nm) radiation on three tropical legumes

Abstract: Tropical regions receive the highest level of global solar ultraviolet (UV) radiation especially UV-B (280-320 nm).The average daily dose of the UV-B radiation in Madurai, South India (10 ~ N) is 10 kJ m -2. This is approximately 50% more than the average daily UV-B radiation in many European countries. A field study was conducted using selective filters to remove either the UV-B (< 320 nm) or UV-B/A (<400 rim) of the solar spectrum, and the effects were followed in Cyamopsis tetragonoloba, Vigna mungo, and Vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 30 publications
1
25
0
1
Order By: Relevance
“…These four cultivars may give better yield only in those latitudes, which receive less of UV-B radiation. Enhancement in the biomass and yield by UV-B exclusion has been recorded earlier in India in Cymopsis, Vigna (Amudha et al, 2005) and soybean variety JS-71-05 (Varalakshmi et al, 2003;Guruprasad et al, 2007).…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…These four cultivars may give better yield only in those latitudes, which receive less of UV-B radiation. Enhancement in the biomass and yield by UV-B exclusion has been recorded earlier in India in Cymopsis, Vigna (Amudha et al, 2005) and soybean variety JS-71-05 (Varalakshmi et al, 2003;Guruprasad et al, 2007).…”
Section: Discussionmentioning
confidence: 81%
“…Whereas cultivars with higher UV-B SI in which the amount of UAS is reduced to lesser extent by exclusion of UV-B (cv. NRC-7, Pusa-24 and PK-1029) the weight of the seeds produced is less (Figure 7) A decrease in UAS was also found in radish and Cyamopsis by the exclusion of UV-B from solar radiation (Zavalla and Botto, 2002;Amudha et al, 2005). Intraspecific differences in the composition and concentration of flavonoids have been shown to determine the UV sensitivity amongst five cultivars of Cucumis sativus (Murali and Teramura, 1986) and in two cultivars of soybean (Murali et al, 1988).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Coleman and Day (2004) have reported that individual leaves as well as total plant leaf area become smaller in cotton plants as the UV-B dose approaches ambient levels compared to sub-optimal levels. Response of cotton plants to UV exclusion is similar to that of mungbean, pea, soybean, barley and Cyamopsis (Pal et al 1997(Pal et al , 2006Mazza et al 1999;Varalakshmi et al 2003;Amudha et al 2005;Guruprasad et al 2007) in terms of enhanced plant height, leaf area and biomass. Exclusion of solar UV reduced the synthesis of UV absorbing substances in the leaves (Table 3).…”
Section: Discussionmentioning
confidence: 67%
“…Such experiments have revealed the sensitivity of several plants to ambient UV. After the exclusion of UV enhancement of growth and biomass has been observed in mung bean, pea, soybean, barley and Cyamopsis (Mazza et al 1999;Pal et al 1997Pal et al , 2006Amudha et al 2005;Varalakshmi et al 2003;Guruprasad et al 2007).…”
Section: Introductionmentioning
confidence: 99%